Tracking Dynamic Tongue Motion in Ultrasound Images for Obstructive Sleep Apnea - Chien, Chih-Yen; Chen, Jeng-Wen; Chang, Chun-Hsiang; Huang, Chih-Chung (Ultrasound in medicine & biology, 2017)
Obstructive sleep apnea (OSA), a breathing disorder characterized by repetitive collapse of the pharyngeal airway during sleep, can cause intermittent hypoxemia and frequent arousal. The evaluation of dynamic tongue motion not only provides the biomechanics and pathophysiology for OSA diagnosis, but also helps doctors to determine treatment strategies for these patients with OSA. The purpose of this study was to develop and verify a dedicated tracking algorithm, called the modified optical flow (OF)-based method, for monitoring the dynamic motion of the tongue base in ultrasound image sequences derived from controls and patients with OSA. The performance of the proposed method was verified by phantom and synthetic data. A common tracking method, the normalized cross-correlation method, was included for comparison. The efficacy of the algorithms was evaluated by calculating the estimated displacement error. All results indicated that the modified OF-based method exhibited higher accuracy in verification experiments. In the human subject experiment, all participants performed the Müller maneuver (MM) to simulate the contour changes of the tongue base with a negative pharyngeal airway pressure in sleep apnea. Ultrasound image sequences of the tongue were obtained during 10 s of a transition from normal breathing to the MM, and these were measured using the modified OF-based method. The results indicated that the displacement of the tongue base during the MM was larger in the controls than in the patients with OSA (p < 0.05); the calculated areas of the tongue in the controls and patients with OSA were 24.9 ± 3.0 and 27.6 ± 3.3 cm2, respectively, during normal breathing (p < 0.05), and 24.7 ± 3.6 and 27.3 ± 3.8 cm2, respectively, at the end of the MM. The percentage changes in the tongue area were 2.2% and 1.3% in the controls and patients with OSA, respectively. We found that quantitative assessment of tongue motion by ultrasound imaging is suitable for evaluating pharyngeal airway behavior in OSA patients with minimal invasiveness and easy accessibility.